The study of the Drosophila innubila nudivirus in cells and flies. - Schedl, M.E.; Mulkey, K.M.; Adewumi, T.S.; Unckless, R.L. (Virology, 2026)
Species of the fruit fly, Drosophila, are essential models for investigating host/virus interactions. Research aimed at understanding how hosts mount immune defenses against viruses and how viruses evade those immune defenses relies on host/virus pairs that have evolved together over time, thus necessitating a need for a DNA virus model system for Drosophila with a virus that naturally infects the host. The Drosophila innubila nudivirus (DiNV) is an emerging model system poised to take on the role as the DNA virus model for Drosophila. In this paper we describe the development of the DiNV model system with animal and cell resources. We describe the development of new Drosophila cell lines, virus titration assays, anti-nucleocapsid antibodies, and injection-based DiNV infections in Drosophila innubila. We find that D. innubila cells can be used to grow DiNV for use in further experiments, and that DiNV grown from D. innubila cells is virulent when injected into adult D. innubila. The resources we have developed enable substantial future research on the DiNV-D. innubila system.